Pseudomonas thermotolerans sp. nov., a thermotolerant species of the genus Pseudomonas sensu stricto - Manaia, C. M. (2011)
A bacterium, strain CM3T, which has an optimal growth temperature of approximately 47 °C and a maximal growth temperature of 55 SC, was isolated from a hexadecane enrichment culture, obtained from a sample of the industrial cooking water of a cork-processing plant. 16S rRNA gene sequence analysis demonstrated that this Gram-negative, aerobic, rod-shaped bacterium is related to species of the genus Pseudomonas. Phosphatidylethanolamine and phosphatidylglycerol were the major polar lipids of this isolate and the total fatty acid methyl ester profile revealed predominantly C16:1 and C18:1 at a growth temperature of 25 SC, whereas, at a growth temperature of 50 SC, C16:0 was the dominant fatty acid. This is the first report of a species of Pseudomonas sensu stricto that may be considered to be truly thermotolerant. Isolate CM3T (¯DSM 14292T¯LMG 21284T) represents the type strain of a novel species of the genus Pseudomonas, named Pseudomonas thermotolerans sp. nov.